2022
DOI: 10.1002/adma.202206994
|View full text |Cite
|
Sign up to set email alerts
|

In situ Observation of Structural Evolution and Phase Engineering of Amorphous Materials during Crystal Nucleation

Abstract: The nucleation pathway determines the structures and thus properties of formed nanomaterials, which is governed by the free energy of the intermediate phase during nucleation. The amorphous structure, as one of the intermediate phases during nucleation, plays an important role in modulating the nucleation pathway. However, the process and mechanism of crystal nucleation from amorphous structures still need to be fully investigated. Here, in situ aberration‐corrected high‐angle annular dark‐field scanning trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Similarly, Han et al investigated the nucleation pathway of amorphous phases using carbon-doped Ru, Rh, and IrCo nanosheets (ultrathin amorphous metal nanosheets) as starting materials. By employing in situ atomic-resolution STEM, they revealed three distinct stages in the formation of atomic nuclei: atom clustering, crystallization leading to lattice-expanded nanocrystals, and relaxation of lattice-expanded nanocrystals resulting in the formation of final nanocrystals (Figure a–c) . The researchers initiated nucleation from precursor/starting materials with intermediate phases (such as the amorphous phase) and manipulated the nucleation pathway by altering the activation energy.…”
Section: Methods For the Controllable Synthesis Of Amorphous Nanomate...mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Han et al investigated the nucleation pathway of amorphous phases using carbon-doped Ru, Rh, and IrCo nanosheets (ultrathin amorphous metal nanosheets) as starting materials. By employing in situ atomic-resolution STEM, they revealed three distinct stages in the formation of atomic nuclei: atom clustering, crystallization leading to lattice-expanded nanocrystals, and relaxation of lattice-expanded nanocrystals resulting in the formation of final nanocrystals (Figure a–c) . The researchers initiated nucleation from precursor/starting materials with intermediate phases (such as the amorphous phase) and manipulated the nucleation pathway by altering the activation energy.…”
Section: Methods For the Controllable Synthesis Of Amorphous Nanomate...mentioning
confidence: 99%
“…The insets show the corresponding FFT patterns, respectively. (a–c) are adapted with permission from ref . Copyright 2022, WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Methods For the Controllable Synthesis Of Amorphous Nanomate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, in cooperation with Hong's and Lin's groups, our group demonstrated that amorphous metal nanosheets could crystallize into the unconventional crystal phases upon electron-beam irradiation via in situ STEM characterizations. 163 Specifically, when amorphous Ru nanosheets doped with C (Figure 21b) were exposed under an electron beam, crystalline Ru domains with the unconventional fcc phase were gradually generated upon irradiation (Figure 21c,d). It was revealed that the formation of fcc-Ru could be ascribed to the migration and accumulation of C atoms on the surface of Ru nanocrystals during the nucleation, which reduced the surface energy of fcc-Ru compared to the thermodynamically stable hcp-Ru.…”
Section: Secondary Growthmentioning
confidence: 99%
“…(f) HAADF-STEM image and (g) corresponding FFT pattern of Rh nanosheets after electron-beam irradiation. Reproduced with permission from ref . Copyright 2022 Wiley-VCH.…”
Section: Phase Engineering In Metal Nanomaterialsmentioning
confidence: 99%